The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1212/cpj.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Sport concussion and attention deficit hyperactivity disorder in student athletes

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is associated with impulsive behavior and inattention, making it a potential risk factor for sport-related concussion (SRC). The objectives of this study were to determine whether ADHD is an antecedent risk factor for SRC and whether ADHD complicates recovery from SRC in youth athletes.MethodsStudent athletes with a history of SRC were evaluated for the presence of ADHD using diagnostic interview and to determine whether ADHD symptoms began before or af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 37 publications
6
35
0
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD), which affects 6.4 million children (Visser et al, 2014) and nearly 2 million young adults in the United States (Kessler et al, 2006), is the most common neurodevelopmental disorder and is characterized by impulsivity, inattention, and hyperactivity (Centers for Disease & Prevention, 2005). ADHD has been shown to be an antecedent risk factor for concussion in high school and college athletes, with the concussion incidence increasing by 1.5-to 5-fold (Biederman et al, 2015;Iaccarino et al, 2018;Liou et al, 2018), accompanied by amplified concussion symptoms, prolonged recovery (Adeyemo et al, 2014), and impaired performance on working memory tasks (Biederman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention-deficit/hyperactivity disorder (ADHD), which affects 6.4 million children (Visser et al, 2014) and nearly 2 million young adults in the United States (Kessler et al, 2006), is the most common neurodevelopmental disorder and is characterized by impulsivity, inattention, and hyperactivity (Centers for Disease & Prevention, 2005). ADHD has been shown to be an antecedent risk factor for concussion in high school and college athletes, with the concussion incidence increasing by 1.5-to 5-fold (Biederman et al, 2015;Iaccarino et al, 2018;Liou et al, 2018), accompanied by amplified concussion symptoms, prolonged recovery (Adeyemo et al, 2014), and impaired performance on working memory tasks (Biederman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We used our soccer heading paradigm (Bevilacqua et al, 2019) to induce 10 controlled subconcussive head impacts while eliminating extraneous influences that is inherent in field studies, such as bodily hits, fatigue, strenuous exercise, and perspiration/hydration. Since individuals with ADHD have shown to respond adversely to concussion compared to non-ADHD counterparts (Adeyemo et al, 2014;Biederman et al, 2015;Iaccarino et al, 2018;Liou et al, 2018), we hypothesized that individuals with ADHD would also have a reduced tolerance to subconcussive head impacts, by exhibiting significant declines in cognitive function and increases in blood biomarker levels after 10 soccer headings, as compared to their non-ADHD counterparts. In addition, we conducted a post-hoc analysis to examine whether the cognitive decline would correlate with elevations in blood biomarkers in individuals with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…More and more work has shown a link between behavioural disorders (such as ADHD) and learning disabilities as contributing factors to concussion symptom and severity presentation [45][46][47][48]. As an example, participants with ADHD were significantly more disabled after suffering a concussion than were control participants without ADHD, even when controlling for age and sex [49][50][51][52][53].…”
Section: Agementioning
confidence: 99%
“…112 A 2017 study by Montenigro et al 113 using former high school and college football players was "the first in the literature to demonstrate a threshold dose-response relationship between estimated cumulative head impact exposure from football and later-life risk for cognitive and neurobehavioral impairment." Recently, Iaccarino et al 114 found that a) ADHD was over-represented in athletes with a sports-related concussion (SRC); b) the age of onset predated the SRC; and c) ADHD increased the risk of sustaining an SRC. The study authors conclude that these findings "…suggest that ADHD is an antecedent risk factor for SRC, is a risk factor for sustaining multiple head injuries, and contributes to complicate recovery from SRC."…”
Section: Ld/adhd Brain Injury and Causationmentioning
confidence: 99%